ANALISIS HUBUNGAN KAUSALITAS PENGANGGURAN, INFLASI DAN PERTUMBUHAN EKONOMI KOTA PALOPO - Ilham Ilham (MUAMALAH, 2015)
This study discusses the relationship of causality unemployment, inflation and economic growth in Palopo. The purpose of this study is 1. Testing the significance of the inflation-unemployment relationship in Palopo 2. Testing the significance of the relationship of unemployment with economic growth in Palopo 3. Test the significance of the relationship of inflation and economic growth in the City of Palopo. This study was included in the quantitative research design of this study include time series model. The results showed that the unemployment 1. Relationship with weak positive inflation, unemployment with negative economic growth and inflation with a very strong positive economic growth weak if using the Pearson product moment correlation test. If using Spearman correlation test, the relationship of unemployment with a strong positive inflation, unemployment with negative economic growth is very strong and inflation with negative economic growth is weak. 2. There is no significant relationship of unemployment with inflation in Palopo, unemployment there is a significant relationship with economic growth in Palopo and there was no significant correlation of inflation with economic growth in the City of Palopo